Desenvolvimento da cochonilha-branca planococcus citri (risso, 1813) (hemiptera: pseudococcidae) em frutíferas - Correa, L.R.B.; Souza, B.; Santa-Cecilia, L.V.C. (My University, 2008)
The citrus mealybug, Planococcus citri is an important pest attacking several crops. Biotic and abiotic factors, as well as the substrate they feed on influence its population. The present study was aimed to study the effect of some feeding substrates on mealybug development in laboratory conditions. Leaf disks of guava, fig and cherimoya were placed individually on an agar film inside a Petri dish. One egg of the insect was confined inside each container, replicated 60 times for each treatment. Containers were kept in a climatized chamber at 25[degree] C, 70 [plus or minus] 10% RH and 12 hours photophase. Insects reared on guava leaves showed a longer nymphal development, while the female longevity was longer on fig leaves. However, no statistical differences were found in the survival index, which showed values higher than 83%, suggesting that all substrates studied here were adequate for the development of P. citri.
Development of the citrus mealybug Planococcus citri (Risso, 1813) (Hemiptera: Pseudococcidae) on different fruit-bearing plants.